2020
DOI: 10.3390/pr8111441
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assisted Extraction of Phenolic Compounds from a Jujube By-Product with Valuable Bioactivities

Abstract: Jujube plant is a potential source of polyphenols with biological propreties. The purpose of this study was to investigate the application of ultrasound technique for extracting phenolic compounds (TPC) from seeds of Zizyphus lotus under optimization conditions based on response surface methodology. A maximum TPC, total flavonoids content (TFC), and total condensed tannins content (TTC) of 2383.10 ± 0.87 mg GAE/100g, 486.50 ± 0.38 mg QE/100g and 15,787.10 ± 0.10 mg CE/100g, respectively obtained under ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…More recently, in our previous work, we found that phenolic compounds extracted from jujube seeds using UAE under a RSM study have shown a higher yield (2383.10 ± 0.87 mg GAE/100g) at applied conditions of 29.01 °C, 15.94 min, ethanol 50.16%, and liquid to solid ratio of 34.10:1 mL/g. This yield was significantly correlated with the antioxidant activities tested against DPPH (EC50 of 0.39 µg/mL) and FRAP (1670.42 ± 6.5 mg/100 g) 82 .…”
Section: Ultrasound-assisted Extraction (Uae) Of Jujube Antioxidantsmentioning
confidence: 71%
“…More recently, in our previous work, we found that phenolic compounds extracted from jujube seeds using UAE under a RSM study have shown a higher yield (2383.10 ± 0.87 mg GAE/100g) at applied conditions of 29.01 °C, 15.94 min, ethanol 50.16%, and liquid to solid ratio of 34.10:1 mL/g. This yield was significantly correlated with the antioxidant activities tested against DPPH (EC50 of 0.39 µg/mL) and FRAP (1670.42 ± 6.5 mg/100 g) 82 .…”
Section: Ultrasound-assisted Extraction (Uae) Of Jujube Antioxidantsmentioning
confidence: 71%
“…Taraxacum officinale is not a single example which describes how important is the type of solvent, the literature abounds in fresh data which underlines the importance of extractant type and its concentration (17)(18)(19). Additional studies are needed to characterize biological activities of these extracts.…”
Section: Results the Catalase Activity Was Different In Diverse Ethanolic Extracts Of Tomentioning
confidence: 99%
“…These effects may be due to the reduction of antioxidant, lipid peroxidation, and anticholesterolemic activity caused by the polyphenols and flavonoids of Jujuba plant extracts [162] . The sonochemical effect on the molecules from the temperature and sonication time on one another proves that the extraction yield for polar molecules in a hydro-alcoholic solvent is increased by extended sonication times [158] .…”
Section: Cardiovascular Health and Antidiabetic Benefits Of Usae Bioa...mentioning
confidence: 95%
“…The Zizyphus lotus HGMR inhibitory activity (anti-lipidemic activity) was evaluated at a concentration of 100 µg/ml, and the ultrasound extracted content showed an activity of 45.41 %, which is higher when compared to that of conventional extraction methods [157] , [158] . Kim et al have shown the improvement of the serum lipid profile of Sprague Dawley male rats upon consumption of water-based extracts of Jujuba seeds for 10 days, and thus these extracts can reduce hyperlipidemia and alleviate the related cardiovascular diseases [159] .…”
Section: Cardiovascular Health and Antidiabetic Benefits Of Usae Bioa...mentioning
confidence: 99%